Using an extended information-motivation-behavioral skills model to explain HPV vaccination intention among men who have sex with men only and men who have sex with men and women - Guiqian Shi; Bing Lin; Haiying Pan; Wei He; Xiaoni Zhong (Taylor & Francis Group, 2024)
ABSTRACTMen who have sex with men and women (MSMW) have been reported to differ in psychosocial and sexual behavior patterns from men who have sex with men only (MSMO). However, results regarding the differences in HPV vaccination intention/behavior were inconclusive. We compared HPV vaccination intention between MSMO and MSMW and analyzed the differences in potentially associated factors in China. MSM participants were recruited online using a snowball sampling method. Cross-sectional data were collected via a questionnaire based on the extended information-motivation-behavioral skills model. Structural equation modeling was conducted to examine the relationship between the variables, followed by multi-group analysis to test differences between groups. Of 914 MSM, 77.68% were MSMO and 22.32% were MSMW. MSMW had a higher rate of reluctance to vaccinate than MSMO (23.53% vs. 16.20%, p = .016). Differences between the two groups were statistically significant in risky sexual behavior, behavioral skills, and promotional attitude. In both groups, promotional attitude was the most significant predictor of vaccination intention. Vaccination intention was directly influenced by motivation and indirectly by risky sexual behavior in MSMO, but not significantly in MSMW. Additionally, the direct effect of information on behavioral skills in MSMW was significantly greater than that in MSMO, but we did not find any effect of behavioral skills on vaccination intention. MSMW had lower vaccination intention than MSMO. MSMO may be influenced by risky sexual behavior and motivation, positively impacting their vaccination intention, unlike MSMW. Targeted strategies could help promote HPV vaccination, especially in MSMW.